Novel mechanisms of macrolide resistance revealed by in vitro selection and genome analysis in Mycoplasma pneumoniae - Wang, Na; Xu, Xiaogang; Xiao, Li; Liu, Yang (Frontiers in Cellular and Infection Microbiology, 2023)
Mycoplasma pneumoniae is an important pathogen causing upper and lower respiratory tract infections in children and other age groups. Macrolides are the recommended treatments of choice for M. pneumoniae infections. However, macrolide resistance in M. pneumoniae is increasing worldwide, which complicates the treatment strategies. The mechanisms of macrolide resistance have been extensively studied focusing on the mutations in 23S rRNA and ribosomal proteins. Since the secondary treatment choice for pediatric patients is very limited, we decided to look for potential new treatment strategies in macrolide drugs and investigate possible new mechanisms of resistance. We performed an in vitro selection of mutants resistant to five macrolides (erythromycin, roxithromycin, azithromycin, josamycin, and midecamycin) by inducing the parent M. pneumoniae strain M129 with increasing concentrations of the drugs. The evolving cultures in every passage were tested for their antimicrobial susceptibilities to eight drugs and mutations known to be associated with macrolide resistance by PCR and sequencing. The final selected mutants were also analyzed by whole-genome sequencing. Results showed that roxithromycin is the drug that most easily induces resistance (at 0.25 mg/L, with two passages, 23 days), while with midecamycin it is most difficult (at 5.12 mg/L, with seven passages, 87 days). Point mutations C2617A/T, A2063G, or A2064C in domain V of 23S rRNA were detected in mutants resistant to the 14- and 15-membered macrolides, while A2067G/C was selected for the 16-membered macrolides. Single amino acid changes (G72R, G72V) in ribosomal protein L4 emerged during the induction by midecamycin. Genome sequencing identified sequence variations in dnaK, rpoC, glpK, MPN449, and in one of the hsdS (MPN365) genes in the mutants. Mutants induced by the 14- or 15-membered macrolides were resistant to all macrolides, while those induced by the 16-membered macrolides (midecamycin and josamycin) remained susceptible to the 14- and 15-membered macrolides. In summary, these data demonstrated that midecamycin is less potent in inducing resistance than other macrolides, and the induced resistance is restrained to the 16-membered macrolides, suggesting a potential benefit of using midecamycin as a first treatment choice if the strain is susceptible.